2020
DOI: 10.1093/geront/gnaa036
|View full text |Cite
|
Sign up to set email alerts
|

The General Self-Efficacy of Older Adults Receiving Care: A Systematic Review and Meta-Analysis

Abstract: Background and Objectives General self-efficacy (GSE) encourages health-promoting behaviors in older adults. It is unsurprising then that older adults receiving health care services are reported to have a greater risk of low GSE than older adults who are not. Despite this, there is currently limited evidence investigating whether the effect differs based on the environment in which care is received. This review aims to determine whether the GSE of older adults is affected by the receipt of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 67 publications
1
23
0
4
Order By: Relevance
“…Calculating the SD then enabled the lower CI for the mean age to be estimated. Similar methods have been reported in previous meta-analyses ( Jotheeswaran et al, 2016 ; Whitehall et al, 2021 ). Moore et al (2015) only reported the mean age of their participants; however, they used the same data set as Jeste et al (2013) which had a lower 95% CI of 76.55 years.…”
Section: Methodssupporting
confidence: 60%
“…Calculating the SD then enabled the lower CI for the mean age to be estimated. Similar methods have been reported in previous meta-analyses ( Jotheeswaran et al, 2016 ; Whitehall et al, 2021 ). Moore et al (2015) only reported the mean age of their participants; however, they used the same data set as Jeste et al (2013) which had a lower 95% CI of 76.55 years.…”
Section: Methodssupporting
confidence: 60%
“…Given that receipt of acute hospital care may diminish the psychological resources of older adults ( Whitehall et al, 2020 ), the aim of this study was to validate the current iteration of the MiC questionnaire with a population of older adults ready for discharge from a medicine of the elderly (MoE) ward.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Participants’ mean general self-efficacy score was only 39% of the range of the scoring spectrum (10–40) thereby depicting a poor level of general self-efficacy. This may be a cause for concern considering the reported adverse effects of poor self-efficacy to health and well-being ( Whitehall et al, 2021 ). Though self-efficacy had been studied in different areas (including balance, falls, exercise, foot care and so on) among older adults ( Levy et al, 2020 ; Sharoni et al, 2018 ; Weiss & Perry, 2020 ), studies on general self-efficacy in this group are rather rare.…”
Section: Discussionmentioning
confidence: 99%